Metallic copper nanoparticles induce apoptosis in a human skin melanoma A-375 cell line. (7th February 2017) - Chakraborty, Ruchira; Basu, Tarakdas
Abstract: In two earlier communications (Chatterjee et al 2012 Nanotechnology 23 085103, Chatterjee et al 2014 Nanotechnology 25 135101 ), we reported the development of a simple and unique method of synthesizing highly stable metallic copper nanoparticles (Cu NPs) with high antibacterial activity. Here we report on the cytotoxic potency of the NPs against cancer cells. The value of the IC50 dose of the Cu NPs against human skin cancer cell A-375 was found to be 1.71 μ g ml −1 only, which was much less than values reported so far, and this concentration had no cytotoxic effect on normal white blood cells. The NPs caused (i) lowering of cell membrane rigidity, (ii) DNA degradation, (iii) chromosomal condensation, (iv) cell cycle arrest in the G2/M phase, (v) depolarization of the mitochondrial membrane and (vi) apoptosis of cells. Cellular apoptosis occurred in the caspase-9-mediated intrinsic pathway. This study revealed that our Cu NPs had high anticancer properties by killing tumor cells through the apoptotic pathway. Since this particle has high antibacterial activity, our Cu NPs might be developed in future as a dual action drug—anticancer as well as antibacterial.